Une expérience de recherche-intervention dans une entreprise d’exploitation minière : défis et possibilités - João César de Freitas Fonseca; José Newton Garcia de Araújo; Carlos Eduardo Carrusca Vieira; Rodrigo Padrini Monteiro (Communiquer)
In this article, the preliminary results of an intervention research in an iron ore extraction company are discussed. The company required the individual development of cable excavator operators in order to increase their productivity. As an alternative proposal, we presented a project focused on the collective dimension of work, while valuing the knowledge of operators and other workers in the local productive system. Their families also participated in the research. Based on qualitative methodologies, we were inspired by work clinics approaches; using interviews, field observation, discussion groups, look-alike instruction, simple and cross-confrontation. The results show that the company, which previously neglected dialogue with its workers, now tends to welcome actions aimed at facilitating the collective dimension of work as well as a relative participation of employees in the local organization of work processes.